2022
DOI: 10.1249/mss.0000000000002984
|View full text |Cite
|
Sign up to set email alerts
|

Moderators of Resistance Training Effects in Overweight and Obese Adults: A Systematic Review and Meta-analysis

Abstract: Purpose: This study aimed to analyze whether the effects of resistance exercise on whole-body fat and lean mass are moderated by exercise dosage (i.e., duration, volume, and intensity), age, body mass index, baseline values, assessment methods, and prescription of aerobic exercise and caloric restriction in overweight/obese adults. Methods: A systematic search was undertaken in 11 databases from inception to December 2020, with an updated search undertaken in April 2022. Eligible randomized controlled trials e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 134 publications
1
7
0
1
Order By: Relevance
“…Regarding the meta-regression results, we did not observe significant associations between resistance training prescription characteristics and changes in body fat percentage. This result partially agrees with previous studies undertaken in overweight/obese adults (46) and healthy adults (81). Therefore, for women with relatively lower BMI or body fat percentage levels, a moderate-intensity resistance training program of ∼72 weekly sets may be necessary to achieve greater reductions in body fat percentage because of greater improvements in lean mass/muscle hypertrophy.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Regarding the meta-regression results, we did not observe significant associations between resistance training prescription characteristics and changes in body fat percentage. This result partially agrees with previous studies undertaken in overweight/obese adults (46) and healthy adults (81). Therefore, for women with relatively lower BMI or body fat percentage levels, a moderate-intensity resistance training program of ∼72 weekly sets may be necessary to achieve greater reductions in body fat percentage because of greater improvements in lean mass/muscle hypertrophy.…”
Section: Discussionsupporting
confidence: 93%
“…For example, we included only nonobese young healthy women, whereas Hagstrom et al (27) included young and middle-aged women regardless of body mass. We previously observed that resistance-based exercise programs result in smaller adaptations in middle-aged compared with young adults (46,48). In addition, we used a three-level metaanalysis, whereas a two-level meta-analysis was used by Hagstrom et al (27).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Por lo tanto, los hallazgos de esta revisión sistemática podrían romper con el pensamiento de que el entrenamiento aeróbico tradicional es el principal medio para perder peso [76], especialmente para la población con sobrepeso y obesidad. Después de todo, el entrenamiento de fuerza puede aumentar la masa magra corporal y la masa muscular además de reducir el %GC [77,78,79,80], mejorando así la composición corporal. Por tal motivo, este hallazgo brinda un fuerte apoyo al entrenamiento de fuerza como una futura forma efectiva de combatir la obesidad, perder grasa y ganar músculo.…”
Section: Discussionunclassified
“…Nevertheless, our exploratory pairwise meta-analysis indicates that aerobic exercise and/or dietary interventions could be useful to significantly reduce fat mass and body weight; however, this is accompanied by a reduction in lean mass in women high risk of breast cancer. Previous exercise and dietary recommendations for adults who are overweight or obese may be useful to improve lean mass and fat mass in this specific subgroup[149][150][151][152] and potentially reduce the risk for future treatment/surgical complications. Second, most studies had a high risk of bias, and this likely affected the precision, magnitude, and certainty of the evidence.…”
mentioning
confidence: 99%